Jehovah's Witnesses : portrait of a contemporary religious movement - Holden, Andrew, 1964- (Routledge, 2002)
This major study reveals the dependency of this movement on the physical and cultural resources which have caused the privatisation of religion, the erosion of community, the separation of 'fact' from supernatural faith and their expansion.